Identify Attributes of Service Quality Factors and Other Factors Affecting Calla SPA Customer Satisfaction - Van Nhan, Nguyen; Hồng Thị Thu Trang; Trần Thị Thúy Vân (SAN Scientific, 2024)
This research aimed to identify the factors influencing customer satisfaction at Calla SPA, focusing on service quality attributes such as Tangibility, Reliability, Ability to meet expectations, and Assurance, as well as other factors like price and location of Calla SPA offices. Both qualitative and quantitative methods were utilized, including document research, in-depth interviews, group discussions, and surveys. Results indicated that service quality (β3) had the strongest impact on satisfaction, followed by price (β1) and location of the SPA (β2). SPSS testing confirmed the reliability of the scale (α = 0.70 to 0.95), with total correlation coefficients above 0.3, KMO values between 0.5 and 1, and significance levels (Sig) below 0.05. These findings provide a foundation for Calla SPA's management to enhance customer satisfaction through service quality improvements, thereby aiding in market share retention, market expansion, and revenue growth. Furthermore, the research contributes to the theoretical understanding of service quality and customer satisfaction within the SPA industry